Organizational Adaptation to Performance Downturns: An Interpretation-Based Perspective - Ford, Jeffrey D.; Baucus, David A. (Academy of Management Review, 1987)
Organizational adaptation to performance downturns has prompted numerous studies. Although these studies have focused on organizational or decision makers' characteristics influencing adaptation, neither the adaptation process nor where in the process these influences operate has been detailed. A conceptual framework for understanding adaptation to performance downturns by incorporating contingency-based literature into an interpretative-based model is described. Factors which inform decision makers' interpretations and response choices are considered and implications of the framework are discussed.